Bibliometric Analysis on Digital Payment Using Lens.org and Vosviewers: A Comparison of Research Between Malaysia and Poland [version 1; peer review: 1 approved, 2 approved with reservations] - Mior Harris Mior Harun; Nor Irvoni Mohd Ishar; Nur Arfah Mustapha; Azlina Hanif; Joanna Duda; Rafal Kusa (Open Research Europe)
An unprecedented surge in digital payments has had a profound effect on the economic development of developing nations. This transition has enabled greater financial inclusion through the provision of banking services to populations that were previously marginalised. In addition, it has reduced reliance on physical currency, thereby improving security and transparency. This bibliometric analysis examines the research on digital payments in Malaysia and Poland, providing a comparative perspective on research patterns and contributions in these two countries. Furthermore, this study offers a comprehensive examination of the research environment in Malaysia and Poland, elucidating the distinct approaches, methodology, and areas of emphasis in each nation. These findings provide useful insights for those interested in championing digital payment initiatives, as well as contributing to a more robust and resilient digital payment framework. As digital payment ecosystems mature, their significance in altering the economic landscape of emerging countries is likely to become more evident in facilitating cross-border knowledge exchange and collaboration.